Recent advances in understanding maternal perinatal mood disorders [version 1; referees: 2 approved] - Thalia Robakis; Eugenia Jernick; Katherine Williams (F1000Research, 2017)
The study of perinatal mental health (mental health during pregnancy and postpartum) is a complex field of study that is of major importance both for the mental and physical health of new mothers and for the neurobehavioral development and long-term functioning of the children they bear. In this review, we cover the most recent additions to this rapidly evolving field. Notable advances include further illumination of the epidemiological patterns and clinical manifestations of perinatal mood disruption; new efficacy data on treatment and prevention; clarifications of the respective contributions of maternal mental illness and psychotropic medication to outcomes of pregnancy, birth, and child development; and updated expert guidelines for screening.